Disease resistance in livestock - Dayal, Shanker; Kaushik, P. (Indian Farming, 2015)
Diseases in livestock have so far been treated by many ways as per the requirement, i.e. symptoms and kind of disease. As in plants, evidence has been found even in animals that genetic variation brings disease resistance in livestock to the extent in which the host animals are susceptible. Genetic improvement for disease resistance in livestock would considerably contribute to reduce the cost of treatment of diseases.